Peculiarities of Application of Innovative Technologies, Forms and Methods in the Professional Training of Intending Handicraft Teachers to Teaching Art and Technical Subjects - Oleksandr Livshun; Victoriіa Khrenova (Pedagogical Discourse, 2017)
In this paper the authors have considered the necessity to implement the latest achievements of pedagogical science, modern forms, methods and innovative technologies in order to improve professional training of intending Handicraft teachers. Analysis of psychological and pedagogical literature has been carried out. The main approaches used by the leading scientists to differently define the notions of «forms of learning organization» and «organizational forms of learning» have been highlighted in this context. The notion of «learning technology» has been explained from the pedagogical and psychological perspectives as the way of interaction between the participants of learning process. Classification of forms of learning organization according to various criteria has been presented. The authors’ personal points of view as to the use of both traditional (classical) and non-standard (innovative) forms of learning organization to form professional readiness of an intending Handicraft teacher have been suggested.Classification of the main methods has been presented and the authors’ ideas of their appropriate selection to boost the formation of intending Handicraft teachers’ professional readiness to teach the Art and Technical subjects have been expressed. The most efficient innovative learning technologies facilitating the formation of the mentioned above intending teacher’s professional readiness have been identified.The conclusion has been made that using various education technologies, forms and methods in training intending Handicraft teachers one can encourage their creative approach to the performed tasks within the future professional activities.Key words: pedagogical sciences, Handicraft, forms of learning organization, learning methods, learning technologies, innovative technologies, professional readiness, achmeological technology.